PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN DALAM MEMBENTUK LOYALITAS PELANGGAN (STUDI KASUS PADA USAHA PONDOK DURIAN PANGERAN PEKANBARU) - Adi Ruslan; Shorea Khaswarina; Fajar Restuhadi (DINAMIKA PERTANIAN, 2015)
The purpose of this research was to highlight the influence of the quality of services on satisfaction in establishing customer loyalty, to determine the relationship factors affecting the quality of services to satisfaction in establishing customer loyalty and to analyze the correlation between satisfaction and loyalty at Pondok Durian Pangeran Pekanbaru. The method samples were selected using nonprobability sampling techniques with a sample size of 150 respondents who shopped more than twice. Analyzes used a structural equation modeling with AMOS program version 22 applied. The results showed that the quality of products, quality of service had a significant effect on satisfaction. Dimensions of the highest influence on satisfaction were significant with a probability value of 0.023 and responsiveness with a probability value of 0.093. The value of the correlation between customer satisfaction and loyalty Pondok Durian Pangeran was 0.956 and had closely relationship between the two variables. Probability value indicated that satisfaction was a factor determining significantly the customer loyalty. Loading factor value on the regression coefficients of each valuable indicator research (> 0.5) and a probability value of loyalty to the satisfaction indicator worth (0.000) imply that significant satisfaction is an indicator of customer loyalty forming at Pondok Durian Pangeran Pekanbaru.